Thomism and the Renewal of Theology. Chenu, Charlier, and their Ressourcement - Mettepenningen, Jürgen (Horizons, 2012)
La nouvelle théologie is often associated with a certain disapprobation of Thomism. Yet in its "first phase," the theological renewal of the Dominicans M.-D. Chenu (Le Saulchoir) and Louis Charlier (Leuven) was founded and justified upon a historical hermeneutics of Thomas' conception of theology. Against neo-Thomism's excessive rationalism, both Chenu and Charlier strove to recover Thomas's reciprocal immanence of faith and theology by reorienting theology towards the revealed Given. Their concrete elaborations of this fundamental aim, however, ran along different lines. For Charlier, actual theology should be positive theology, regulated by collective faith as expressed in the official teaching of the Magisterium. Chenu on the other hand upholds a theology—both positive and speculative—animated by the theologian's subjective perception of faith. These differences reveal that Chenu and Charlier belong to different theological schools with their own theological traditions: the speculative-theological tradition of Le Sauchoir (A. Gardeil) versus the positive-theological tradition of Leuven (R. Draguet).